Asuhan Akupunktur Pada Penderita Hemoroid di Klinik Assyifa Medika Bogor - Ado Sadroi; Mayang Wulandari; Chantika Mahadini; Leny Candra Kurniawan (Malahayati Nursing Journal, 2026)
ABSTRACT Hemorrhoids are the dilation and inflammation of venous blood vessels in the anal region, originating from the hemorrhoidal plexus, and constitute a condition that can interfere with daily activities and reduce an individual’s quality of life. Acupuncture plays a role in inhibiting pain and regulating autonomic nerve stimulation, particularly the sympathetic nervous system, thereby improving dilated venous blood vessels. This case study aimed to determine the benefits of acupuncture care for a patient with hemorrhoids at Assyifa Medika Clinic, Bogor. The study was conducted as a single case study over six therapy sessions involving one male participant aged 40 years who had experienced hemorrhoids for one month. Data collection techniques included observation (Wang), interview (Wen), listening and smelling (Wen), and palpation (Qie) in accordance with Traditional Chinese Medicine (TCM) standards. The selection of acupuncture points was based on the syndrome of Damp-Heat in the Lower Jiao, with the therapeutic principle of clearing heat and dampness. The evaluation results showed gradual and consistent improvement, a progressive reduction in pain, improved bowel movement patterns, and the disappearance of the sensation of incomplete defecation by the final therapy session. Keywords: Hemorrhoids, Acupuncture Therapy, Damp-Heat in the Lower Jiao.  ABSTRAK Hemoroid merupakan pelebaran dan inflamasi pembuluh darah vena di daerah anus, berasal dari plexus hemorrhoidalis yang merupakan suatu penyakit berbahaya dan dapat mengganggu aktivitas sehari-hari sehingga mengakibatkan penurunan kualitas hidup seseorang. Akupunktur berperan dalam menghambat nyeri dan meregulasi rangsangan saraf otonom terutama saraf simpatis sehingga dapat memperbaiki pembuluh darah vena yang melebar. Penelitian studi kasus ini bertujuan untuk mengetahui manfaat Asuhan Akupunktur pada Penderita Hemoroid di Klinik Assyifa Medika Bogor. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu orang partisipan laki-laki berusia 40 tahun yang mengalami Hemoroid sejak 1 bulan yang lalu. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Lembab Panas di Jiao Bawah dengan prinsip terapi yang diterapkan adalah Membersihkan panas dan lembap. Hasil evaluasi terapi menunjukkan adanya perbaikan yang bertahap dan konsisten, berkurangnya nyeri secara bertahap, membaiknya pola buang air besar, serta hilangnya rasa tidak tuntas setelah BAB pada sesi terapi akhir. Kata Kunci: Hemoroid, Terapi Akupunktur, Lembab Panas di Jiao Bawah.